Tumor-Induced T Cell Polarization by Schwann Cells - Galina V. Shurin; Kavita Vats; Oleg Kruglov; Yuri L. Bunimovich; Michael R. Shurin (Cells, 2022)
Nerve-cancer crosstalk resulting in either tumor neurogenesis or intratumoral neurodegeneration is critically controlled by Schwann cells, the principal glial cells of the peripheral nervous system. Though the direct stimulating effect of Schwann cells on malignant cell proliferation, motility, epithelial–mesenchymal transition, and the formation of metastases have been intensively investigated, the ability of Schwann cells to affect the effector and regulatory immune cells in the tumor environment is significantly less studied. Here, we demonstrated that tumor cells could stimulate Schwann cells to produce high levels of prostaglandin E, which could be blocked by COX-2 inhibitors. This effect was mediated by tumor-derived TGF-β as neutralization of this cytokine in the tumor-conditioned medium completely blocked the inducible prostaglandin E production by Schwann cells. Similar protective effects were also induced by the Schwann cell pretreatment with TGF-βR1/ALK4/5/7 and MAPK/ERK kinase inhibitors of the canonical and non-canonical TGF-β signaling pathways, respectively. Furthermore, prostaglandin E derived from tumor-activated Schwann cells blocked the proliferation of CD3/CD28-activated T cells and upregulated the expression of CD73 and PD-1 on both CD4+ and CD8+ T cells, suggesting T cell polarization to the exhausted phenotype. This new pathway of tumor-induced T cell inhibition via the activation of neuroglial cells represents new evidence of the importance of nerve–cancer crosstalk in controlling tumor development and progression. A better understanding of the tumor-neuro-immune axis supports the development of efficient targets for harnessing this axis and improving the efficacy of cancer therapy.